Parallelism of syntax and semantics in English - Vietnamese proverbs - Pham, Hang Thu; Pham, Quynh Thi Huong (Edelweiss Applied Science and Technology, 2025)
Parallelism is a fairly typical rhetorical device in proverbs. This type of structure is effective in expressing content as well as creating artistic effects for proverbs. This article aims to understand the parallelism in English proverbs and Vietnamese proverbs on both aspects of semantic parallelism and syntactic parallelism. Through the survey, semantic parallelism is considered on three aspects: similarity relationship, contrast relationship, inter-causal/ dependence relationship; Syntactic parallelism is considered in eight aspects: lexical repetition, preposition/prepositional phrase repetition, noun/noun phrase repetition, adjective/adjective phrase repetition, verb/verb phrase repetition words, predicate repetition, clause repetition, complex sentence repetition. Discovering the structure of semantic parallelism and syntactic parallelism in English and Vietnamese proverbs helps to better understand the cultural identity of each nation.